TECHNICAL INNOVATIONS AND OPTIMIZATIONS ON THE EXTERNAL GEARSHIFT MECHANISM - Lucian, Campan Dan (European Scientific Journal, ESJ, 2014)
The gearshift mechanism is an essential subcomponent of the car. It is used on the majority of vehicles with manual transmission. Along with the improvement of the transmission it is also needed an improvement of the system witch actuates the changing of the gears. Therefore in this paper I had represented a new solution of mechanism which can be used for changing the gears at the next generation of shifters.